2021
DOI: 10.1039/d0ra09131f
|View full text |Cite
|
Sign up to set email alerts
|

A piezoelectric poly(vinylidene fluoride) tube featuring highly-sensitive and isotropic piezoelectric output for compression

Abstract: A PVDF tube exhibited a highly-sensitive and isotropic piezoelectric output for multi-stresses from any directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…1,2 Due to the ability to realize the mutual conversion of mechanical energy and electrical energy, [3][4][5] piezoelectric materials have aroused great interest in practical applications, and are widely used in sensing, energy storage, electronics and other elds. 6,7 For example, Li et al 8 demonstrated a non-lead (ZnO) piezoelectric device powered by heart movement. Cheng et al 9 reported a self-powered PVDF sensor for blood pressure monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to the ability to realize the mutual conversion of mechanical energy and electrical energy, [3][4][5] piezoelectric materials have aroused great interest in practical applications, and are widely used in sensing, energy storage, electronics and other elds. 6,7 For example, Li et al 8 demonstrated a non-lead (ZnO) piezoelectric device powered by heart movement. Cheng et al 9 reported a self-powered PVDF sensor for blood pressure monitoring.…”
Section: Introductionmentioning
confidence: 99%